THE USE OF ENGLISH LEARNING CONTENTS ON INSTAGRAM FOR IMPROVING ENGLISH SPEAKING SKILLS AMONG EFL STUDENTS' PERCEPTION - Nur Khasanah (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2023)
This study investigates the effectiveness of using Instagram as a digital platform for English language learning, focusing on its impact on students' speaking skills at UIN Walisongo. Based on the responses of 86 EFL students, the research explores Instagram usage patterns, motivations, and perceived benefits. The findings reveal a positive inclination towards English learning accounts, interactive learning, and connecting with English-speaking users. The study reveals regular engagement with speaking skills through Instagram content, highlighting its potential for language practice. While students generally view Instagram positively, challenges such as limited practice time and content relevance are acknowledged. Recommendations for improvement include more interactive tools and diverse content. The study provides valuable insights into the use of Instagram for language learning and offers practical recommendations for increasing the platform's effectiveness.